2020
DOI: 10.1038/s41598-020-66668-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sudden cardiac arrest and ventricular arrhythmia with sulfonylureas: An experience with conceptual replication in two independent populations

Abstract: Sulfonylureas are commonly used to treat type 2 diabetes mellitus. Despite awareness of their effects on cardiac physiology, a knowledge gap exists regarding their effects on cardiovascular events in real-world populations. Prior studies reported sulfonylurea-associated cardiovascular death but not serious arrhythmogenic endpoints like sudden cardiac arrest (ScA) or ventricular arrhythmia (VA). We assessed the comparative real-world risk of ScA/VA among users of second-generation sulfonylureas: glimepiride, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…No studies reported sudden cardiac death as an individual endpoint. One study at a moderate risk of bias using US Medicaid claims data conducted an intraclass comparison, reporting an increased risk for a composite end point of sudden cardiac death and fatal VA among glimepiride users (aHR: 1.33, 95% CI: 1.02–1.75) and no association among glyburide users (aHR: 0.91, 95% CI: 0.72–1.20), both relative to glipizide 16 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No studies reported sudden cardiac death as an individual endpoint. One study at a moderate risk of bias using US Medicaid claims data conducted an intraclass comparison, reporting an increased risk for a composite end point of sudden cardiac death and fatal VA among glimepiride users (aHR: 1.33, 95% CI: 1.02–1.75) and no association among glyburide users (aHR: 0.91, 95% CI: 0.72–1.20), both relative to glipizide 16 …”
Section: Resultsmentioning
confidence: 99%
“…After applying the ROBINS-I tool, 2 studies were assigned a moderate risk of bias, 16,17 4 studies were assigned a serious risk of bias, [18][19][20][21] and 11 studies were assigned a critical risk of bias 19,[22][23][24][25][26][27][28][29][30][31] (Table 3, Figure 2). The domain "'risk of bias due to confounding"' was one of the ROBINS-I domains most responsible for the overall risk of bias.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several population-based OHCA studies have been conducted using administrative databases in the US 20–24 and outside the US 7 , 25 , 26 based on the above-mentioned validated OHCA-related diagnostic codes. However, because coding practices and reimbursement policies may differ across healthcare systems, it should not be taken for granted that the validity of case definitions established in one database can be extrapolated to another database.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the risk of VA/SCD differed by choice of sulfonylurea (55)(56)(57)(58). Further research comparing risk of VA/SCD between different drugs of the sulfonylurea class is warranted, such that clinicians can avoid choosing sulfonylurea with high arrhythmogenic risk.…”
Section: Study Limitationsmentioning
confidence: 99%